Quality of life analysis of families having deaf children assisted in a reference center of the Unified Health System - Barreto Nascimento, Gicélia; de Oliveira Schiling, Nilvana; Ribeiro Ubal, Simone; Pinto Vieira Biaggio, Eliara; Kessler, Themis Maria (O Mundo da Saúde, 2016)
The family plays a fundamental role in promoting the health of their children. Regarding hearing impairment, the interaction between deaf family-child dyad enables the appropriate language development, social and emotional of the child. For this a good quality of family life is essential. This study aimed to investigate the perception of quality of life for families who have a member with a hearing impairment and relate with everyday communication. The study included 20 families of hearing impaired children who attend a middle complexity center of reference in the Health-SUS System. In the research were used the questionnaire of quality of life (WHOQOL-BREF) and “Everyday Things that Interfere with Communication between Families and Individuals with Hearing Impairment”, developed by the researchers. There was a correlation between quality of life and interference with communication in deaf-child dyad family in all domains of WHOQOL-BREF. The greater the perception in the physical domain, the less communicative difficulties in the presence of electronics noise. The higher the psychological domain, the less interference from electronic and competitive speech communication. The less the social field, the less interference from noise electronics, competitive speech and absence of orofacial reading communication. Finally, the higher the environmental sphere, the less interference from electronics communication. It is concluded that investigate the quality of life of the family can help in the planning and development of therapeutic strategies, maximizing the family and child well-being through more contextualized interventions the reality of the patient.